2014
DOI: 10.5751/es-05633-190122
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem Services and Abrupt Transformations in a Coastal Wetland Social-Ecological System: Tubul-Raqui after the 2010 Earthquake in Chile

Abstract: ABSTRACT. Natural disasters can trigger sudden transformations and move ecosystems to different states where the provision of ecosystem services is altered. These changes in ecosystem services affect local communities' well-being and challenge users' adaptation capacities. We used the ecosystem services framework to understand the impacts of abrupt transformations, in a coastal wetland, associated to a ~ 1.6 meter coseismic uplift after an 8.8 magnitude earthquake in Chile. Using mixed methods we (1) identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Finally, despite the substantial physical and environmental disturbances resulting from the tsunami, pelillo extraction exhibited a gradual recovery in 2012, which is supported by recovery of the physical structure of the habitat and the aquatic biota two years after the event in Reference [39]. However, Aswani et al [14] indicated that social recovery was not always concurrent with environmental recovery, which is undoubtedly related to the perception level of the population; possibly, this environmental recovery will influence the recovery of balance in the exploitation of ES in the Tubul-Raqui wetland, as evidenced by Marín et al [54].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Finally, despite the substantial physical and environmental disturbances resulting from the tsunami, pelillo extraction exhibited a gradual recovery in 2012, which is supported by recovery of the physical structure of the habitat and the aquatic biota two years after the event in Reference [39]. However, Aswani et al [14] indicated that social recovery was not always concurrent with environmental recovery, which is undoubtedly related to the perception level of the population; possibly, this environmental recovery will influence the recovery of balance in the exploitation of ES in the Tubul-Raqui wetland, as evidenced by Marín et al [54].…”
Section: Discussionmentioning
confidence: 93%
“…A similar situation (high social perception) regarding regulating services occurred in the habitat for species service, in the study of Marín et al [54], carried out 18 months after the earthquake, the diversity of bird species was one of the most important ES perceived by the inhabitants of the Tubul-Raqui fishing village. This perception can be linked to daily observations of the abundant biodiversity provided by the wetland, including local and migratory bird species (83), micromammals (4), reptiles (6), and amphibians (1), which provides a unique sense of landscape beauty.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such analyses allow modelers to estimate which combinations of ESs are possible given biophysical constraints. On another hand, a range of qualitative and quantitative valuation methods help elicit what matters to people (Klain and Chan, 2012;Marín et al, 2014;Gould et al, 2015) and explore how ESs underpin human wellbeing (Bratman et al, 2012;Hicks and Cinner, 2014;Bratman et al, 2015;Hicks et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Drawing from socio-technological systems thinking, transitions may be fast or slow, intentional or forced, proactive or reactive, planned or surprising and are often associated with resultant regime shifts and tipping points, i.e., moments of system alteration where rapid change could take place (Geels and Schot 2007). For example, Wallace and Wallace 2008, Ernstson et al 2010, Smith and Sterling 2010, Markard et al 2012 describe the conditions of transitions in urbanized settings and other human https://www.ecologyandsociety.org/vol22/iss2/art38/ Bentley et al 2014, Marin et al 2014, Rocha et al 2015 describe the conditions of tipping points and abrupt shifts within social and social-ecological systems. Resultant regime shifts are associated with large and persistent changes in the structure and function of a system that are often only recognizable after the fact.…”
Section: Four Risk Management Regimesmentioning
confidence: 99%